Difference between revisions of "New monads/MonadRandom"
m (transformer formatting) 
(→Connection to stochastics: fix do block code indentation) 

(22 intermediate revisions by 9 users not shown)  
Line 1:  Line 1:  
[[Category:Code]] 
[[Category:Code]] 

−  From New monads, copied from [http://haskell.org/hawiki/MonadRandom old wiki]. 

+  [[Category:Mathematics]] 

−  
−  = MonadRandom = 

A simple monad transformer to allow computations in the transformed monad to generate random values. 
A simple monad transformer to allow computations in the transformed monad to generate random values. 

−  
+  ==The code== 

−  [http://haskell.org/hawiki/CaleGibbard_2fBSDLicense "CaleGibbard/BSDLicense"] 

+  <haskell>{#LANGUAGE MultiParamTypeClasses, UndecidableInstances #} 

−  
+  {#LANGUAGE GeneralizedNewtypeDeriving, FlexibleInstances #} 

−  
+  
−  <haskell> 

−  {# OPTIONS_GHC fglasgowexts #} 

−  
module MonadRandom ( 
module MonadRandom ( 

MonadRandom, 
MonadRandom, 

getRandom, 
getRandom, 

getRandomR, 
getRandomR, 

−  +  getRandoms, 

+  getRandomRs, 

+  evalRandT, 

evalRand, 
evalRand, 

evalRandIO, 
evalRandIO, 

fromList, 
fromList, 

−  Rand, 
+  Rand, RandT  but not the data constructors 
) where 
) where 

−  
+  
import System.Random 
import System.Random 

import Control.Monad.State 
import Control.Monad.State 

import Control.Monad.Identity 
import Control.Monad.Identity 

−  
+  import Control.Monad.Writer 

+  import Control.Monad.Reader 

+  import Control.Arrow 

+  
class (Monad m) => MonadRandom m where 
class (Monad m) => MonadRandom m where 

−  getRandom :: (Random a) => m a 
+  getRandom :: (Random a) => m a 
−  +  getRandoms :: (Random a) => m [a] 

−  +  getRandomR :: (Random a) => (a,a) > m a 

−  +  getRandomRs :: (Random a) => (a,a) > m [a] 

+  
+  newtype RandT g m a = RandT (StateT g m a) 

deriving (Functor, Monad, MonadTrans, MonadIO) 
deriving (Functor, Monad, MonadTrans, MonadIO) 

−  
+  
liftState :: (MonadState s m) => (s > (a,s)) > m a 
liftState :: (MonadState s m) => (s > (a,s)) > m a 

liftState t = do v < get 
liftState t = do v < get 

Line 39:  Line 37:  
put v' 
put v' 

return x 
return x 

−  
+  
−  instance (Monad m, RandomGen g) => MonadRandom ( 
+  instance (Monad m, RandomGen g) => MonadRandom (RandT g m) where 
−  getRandom = 
+  getRandom = RandT $ liftState random 
−  +  getRandoms = RandT $ liftState $ first randoms . split 

−  +  getRandomR (x,y) = RandT $ liftState $ randomR (x,y) 

−  +  getRandomRs (x,y) = RandT $ liftState $ 

−  +  first (randomRs (x,y)) . split 

−  +  
+  evalRandT :: (Monad m, RandomGen g) => RandT g m a > g > m a 

+  evalRandT (RandT x) g = evalStateT x g 

+  
+  runRandT :: (Monad m, RandomGen g) => RandT g m a > g > m (a, g) 

+  runRandT (RandT x) g = runStateT x g 

+  
 Boring random monad :) 
 Boring random monad :) 

−  newtype Rand g a = Rand 
+  newtype Rand g a = Rand (RandT g Identity a) 
deriving (Functor, Monad, MonadRandom) 
deriving (Functor, Monad, MonadRandom) 

−  
+  
evalRand :: (RandomGen g) => Rand g a > g > a 
evalRand :: (RandomGen g) => Rand g a > g > a 

−  evalRand x g = runIdentity ( 
+  evalRand (Rand x) g = runIdentity (evalRandT x g) 
−  +  
+  runRand :: (RandomGen g) => Rand g a > g > (a, g) 

+  runRand (Rand x) g = runIdentity (runRandT x g) 

+  
evalRandIO :: Rand StdGen a > IO a 
evalRandIO :: Rand StdGen a > IO a 

−  evalRandIO x = getStdRandom (runIdentity . runStateT 
+  evalRandIO (Rand (RandT x)) = getStdRandom (runIdentity . runStateT x) 
−  +  
fromList :: (MonadRandom m) => [(a,Rational)] > m a 
fromList :: (MonadRandom m) => [(a,Rational)] > m a 

fromList [] = error "MonadRandom.fromList called with empty list" 
fromList [] = error "MonadRandom.fromList called with empty list" 

fromList [(x,_)] = return x 
fromList [(x,_)] = return x 

−  fromList xs = do let s = fromRational $ sum (map snd xs)  total weight 

+  fromList xs = do 

−  +  let total = fromRational $ sum (map snd xs) :: Double  total weight 

−  +  cumulative = scanl1 (\(x,q) (y,s) > (y, s+q)) xs  cumulative weights 

−  +  p < liftM toRational $ getRandomR (0.0, total) 

+  return $ fst . head . dropWhile (\(x,q) > q < p) $ cumulative 

</haskell> 
</haskell> 

−  
+  To make use of common transformer stacks involving Rand and RandT, the following definitions may prove useful: 

−  To make use of common transformer stacks involving Rand and RandomT, the following definitions may prove useful: 

<haskell> 
<haskell> 

instance (MonadRandom m) => MonadRandom (StateT s m) where 
instance (MonadRandom m) => MonadRandom (StateT s m) where 

getRandom = lift getRandom 
getRandom = lift getRandom 

−  getRandomR 
+  getRandomR = lift . getRandomR 
+  getRandoms = lift getRandoms 

+  getRandomRs = lift . getRandomRs 

instance (MonadRandom m, Monoid w) => MonadRandom (WriterT w m) where 
instance (MonadRandom m, Monoid w) => MonadRandom (WriterT w m) where 

getRandom = lift getRandom 
getRandom = lift getRandom 

−  getRandomR 
+  getRandomR = lift . getRandomR 
+  getRandoms = lift getRandoms 

+  getRandomRs = lift . getRandomRs 

instance (MonadRandom m) => MonadRandom (ReaderT r m) where 
instance (MonadRandom m) => MonadRandom (ReaderT r m) where 

getRandom = lift getRandom 
getRandom = lift getRandom 

−  getRandomR 
+  getRandomR = lift . getRandomR 
+  getRandoms = lift getRandoms 

+  getRandomRs = lift . getRandomRs 

−  
+  instance (MonadState s m, RandomGen g) => MonadState s (RandT g m) where 

−  instance (MonadState s m, RandomGen g) => MonadState s (RandomT g m) where 

get = lift get 
get = lift get 

−  put 
+  put = lift . put 
−  instance (MonadReader r m, RandomGen g) => MonadReader r ( 
+  instance (MonadReader r m, RandomGen g) => MonadReader r (RandT g m) where 
ask = lift ask 
ask = lift ask 

−  local f m = 
+  local f (RandT m) = RandT $ local f m 
−  instance (MonadWriter w m, RandomGen g, Monoid w) => MonadWriter w ( 
+  instance (MonadWriter w m, RandomGen g, Monoid w) => MonadWriter w (RandT g m) where 
−  tell 
+  tell = lift . tell 
−  listen m = 
+  listen (RandT m) = RandT $ listen m 
−  pass m = 
+  pass (RandT m) = RandT $ pass m 
</haskell> 
</haskell> 

+  
+  You may also want a MonadRandom instance for IO: 

+  
+  <haskell> 

+  instance MonadRandom IO where 

+  getRandom = randomIO 

+  getRandomR = randomRIO 

+  getRandoms = fmap randoms newStdGen 

+  getRandomRs b = fmap (randomRs b) newStdGen 

+  
+  </haskell> 

+  
+  == Connection to stochastics == 

+  
+  There is some correspondence between notions in programming and in mathematics: 

+  
+  { 

+   

+  random generator  ~  random variable / probabilistic experiment 

+   

+  result of a random generator  ~  outcome of a probabilistic experiment 

+  } 

+  
+  Thus the signature 

+  <haskell>rx :: (MonadRandom m, Random a) => m a</haskell> 

+  can be considered as "<hask>rx</hask> is a random variable". In the donotation the line 

+  <haskell>x < rx</haskell> 

+  means that "<hask>x</hask> is an outcome of <hask>rx</hask>". 

+  
+  In a language without higher order functions and using a random 

+  generator "function" it is not possible to work with random variables, it 

+  is only possible to compute with outcomes, e.g. <code>rand()+rand()</code>. In a 

+  language where random generators are implemented as objects, computing 

+  with random variables is possible but still cumbersome. 

+  
+  In Haskell we have both options either computing with outcomes 

+  <haskell> 

+  do x < rx 

+  y < ry 

+  return (x+y) 

+  </haskell> 

+  or computing with random variables 

+  <haskell> 

+  liftM2 (+) rx ry 

+  </haskell> 

+  
+  This means that <hask>liftM</hask> like functions convert ordinary arithmetic into 

+  random variable arithmetic. But there is also some arithmetic on random 

+  variables which can not be performed on outcomes. For example, given a 

+  function that repeats an action until the result fulfills a certain 

+  property (I wonder if there is already something of this kind in the 

+  standard libraries) 

+  <haskell> 

+  untilM :: Monad m => (a > Bool) > m a > m a 

+  untilM p m = 

+  do x < m 

+  if p x then return x else untilM p m 

+  </haskell> 

+  we can suppress certain outcomes of an experiment. E.g. if 

+  <haskell> 

+  getRandomR (10,10) 

+  </haskell> 

+  is a uniformly distributed random variable between −10 and 10, then 

+  <haskell> 

+  untilM (0/=) (getRandomR (10,10)) 

+  </haskell> 

+  is a random variable with a uniform distribution of {−10, …, −1, 1, …, 10}. 

+  
+  ==See also== 

+  * <hask>Arbitrary</hask> type class of [[Introduction to QuickCheckQuickcheck]] 

+  * http://www.haskell.org/pipermail/haskellcafe/2005May/009775.html 

+  * [[New monads/MonadRandomSplittable]] 

+  * [http://hackage.haskell.org/packages/archive/pkglist.html#cat:Control The package list of Hackage] 

+  * [http://hackage.haskell.org/cgibin/hackagescripts/package/MonadRandom The MonadRandom package on Hackage] 

+  * http://code.haskell.org/monadrandom/ 
Latest revision as of 13:41, 2 April 2019
A simple monad transformer to allow computations in the transformed monad to generate random values.
The code
{#LANGUAGE MultiParamTypeClasses, UndecidableInstances #}
{#LANGUAGE GeneralizedNewtypeDeriving, FlexibleInstances #}
module MonadRandom (
MonadRandom,
getRandom,
getRandomR,
getRandoms,
getRandomRs,
evalRandT,
evalRand,
evalRandIO,
fromList,
Rand, RandT  but not the data constructors
) where
import System.Random
import Control.Monad.State
import Control.Monad.Identity
import Control.Monad.Writer
import Control.Monad.Reader
import Control.Arrow
class (Monad m) => MonadRandom m where
getRandom :: (Random a) => m a
getRandoms :: (Random a) => m [a]
getRandomR :: (Random a) => (a,a) > m a
getRandomRs :: (Random a) => (a,a) > m [a]
newtype RandT g m a = RandT (StateT g m a)
deriving (Functor, Monad, MonadTrans, MonadIO)
liftState :: (MonadState s m) => (s > (a,s)) > m a
liftState t = do v < get
let (x, v') = t v
put v'
return x
instance (Monad m, RandomGen g) => MonadRandom (RandT g m) where
getRandom = RandT $ liftState random
getRandoms = RandT $ liftState $ first randoms . split
getRandomR (x,y) = RandT $ liftState $ randomR (x,y)
getRandomRs (x,y) = RandT $ liftState $
first (randomRs (x,y)) . split
evalRandT :: (Monad m, RandomGen g) => RandT g m a > g > m a
evalRandT (RandT x) g = evalStateT x g
runRandT :: (Monad m, RandomGen g) => RandT g m a > g > m (a, g)
runRandT (RandT x) g = runStateT x g
 Boring random monad :)
newtype Rand g a = Rand (RandT g Identity a)
deriving (Functor, Monad, MonadRandom)
evalRand :: (RandomGen g) => Rand g a > g > a
evalRand (Rand x) g = runIdentity (evalRandT x g)
runRand :: (RandomGen g) => Rand g a > g > (a, g)
runRand (Rand x) g = runIdentity (runRandT x g)
evalRandIO :: Rand StdGen a > IO a
evalRandIO (Rand (RandT x)) = getStdRandom (runIdentity . runStateT x)
fromList :: (MonadRandom m) => [(a,Rational)] > m a
fromList [] = error "MonadRandom.fromList called with empty list"
fromList [(x,_)] = return x
fromList xs = do
let total = fromRational $ sum (map snd xs) :: Double  total weight
cumulative = scanl1 (\(x,q) (y,s) > (y, s+q)) xs  cumulative weights
p < liftM toRational $ getRandomR (0.0, total)
return $ fst . head . dropWhile (\(x,q) > q < p) $ cumulative
To make use of common transformer stacks involving Rand and RandT, the following definitions may prove useful:
instance (MonadRandom m) => MonadRandom (StateT s m) where
getRandom = lift getRandom
getRandomR = lift . getRandomR
getRandoms = lift getRandoms
getRandomRs = lift . getRandomRs
instance (MonadRandom m, Monoid w) => MonadRandom (WriterT w m) where
getRandom = lift getRandom
getRandomR = lift . getRandomR
getRandoms = lift getRandoms
getRandomRs = lift . getRandomRs
instance (MonadRandom m) => MonadRandom (ReaderT r m) where
getRandom = lift getRandom
getRandomR = lift . getRandomR
getRandoms = lift getRandoms
getRandomRs = lift . getRandomRs
instance (MonadState s m, RandomGen g) => MonadState s (RandT g m) where
get = lift get
put = lift . put
instance (MonadReader r m, RandomGen g) => MonadReader r (RandT g m) where
ask = lift ask
local f (RandT m) = RandT $ local f m
instance (MonadWriter w m, RandomGen g, Monoid w) => MonadWriter w (RandT g m) where
tell = lift . tell
listen (RandT m) = RandT $ listen m
pass (RandT m) = RandT $ pass m
You may also want a MonadRandom instance for IO:
instance MonadRandom IO where
getRandom = randomIO
getRandomR = randomRIO
getRandoms = fmap randoms newStdGen
getRandomRs b = fmap (randomRs b) newStdGen
Connection to stochastics
There is some correspondence between notions in programming and in mathematics:
random generator  ~  random variable / probabilistic experiment 
result of a random generator  ~  outcome of a probabilistic experiment 
Thus the signature
rx :: (MonadRandom m, Random a) => m a
can be considered as "rx
is a random variable". In the donotation the line
x < rx
means that "x
is an outcome of rx
".
In a language without higher order functions and using a random
generator "function" it is not possible to work with random variables, it
is only possible to compute with outcomes, e.g. rand()+rand()
. In a
language where random generators are implemented as objects, computing
with random variables is possible but still cumbersome.
In Haskell we have both options either computing with outcomes
do x < rx
y < ry
return (x+y)
or computing with random variables
liftM2 (+) rx ry
This means that liftM
like functions convert ordinary arithmetic into
random variable arithmetic. But there is also some arithmetic on random
variables which can not be performed on outcomes. For example, given a
function that repeats an action until the result fulfills a certain
property (I wonder if there is already something of this kind in the
standard libraries)
untilM :: Monad m => (a > Bool) > m a > m a
untilM p m =
do x < m
if p x then return x else untilM p m
we can suppress certain outcomes of an experiment. E.g. if
getRandomR (10,10)
is a uniformly distributed random variable between −10 and 10, then
untilM (0/=) (getRandomR (10,10))
is a random variable with a uniform distribution of {−10, …, −1, 1, …, 10}.